2009
DOI: 10.1002/lary.20158
|View full text |Cite
|
Sign up to set email alerts
|

Histologic study of gore‐tex removed after rhinoplasty

Abstract: In contrast to previous studies, our study showed that Gore-Tex samples implanted in human bodies for extended periods of time prompted ingrowth of neighboring tissues, calcified tissue degeneration, and inflammation. Foreign body reactions were found in a large number of samples. The Gore-Tex structures were destroyed and transformed. As a result, it is important to follow the stability of Gore-Tex material on a long-term basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 15 publications
1
21
0
1
Order By: Relevance
“…Implants made of ePTFE are more widely accepted by rhinoplastic surgeons, but recent histologic studies have suggested that ePTFE may elicit greater foreign body reactions than previously suspected. 3 It also remains unknown whether complications are more common when ePTFE is used simultaneously with pHDPE. A recent meta-analysis of available alloplasts concluded that improved reporting of adverse outcomes is necessary before any firm conclusions can be made regarding safety and efficacy.…”
Section: Hile Autologousmentioning
confidence: 99%
“…Implants made of ePTFE are more widely accepted by rhinoplastic surgeons, but recent histologic studies have suggested that ePTFE may elicit greater foreign body reactions than previously suspected. 3 It also remains unknown whether complications are more common when ePTFE is used simultaneously with pHDPE. A recent meta-analysis of available alloplasts concluded that improved reporting of adverse outcomes is necessary before any firm conclusions can be made regarding safety and efficacy.…”
Section: Hile Autologousmentioning
confidence: 99%
“…In this study, 77% of all capsular contracture cases were related to the usage of silicone implants. Calcinosis of both type of implants has also been reported, however the data are very limited [29,30]. This study did not compare these complications due to their rarity and low reporting rate.…”
Section: Discussionmentioning
confidence: 91%
“…Informed consent was obtained. The plastic surgeon removed the Gore-Tex material [1][2][3], and sent it for histologic examination. Our H&E staining was performed as previously described [4].…”
Section: Sirmentioning
confidence: 99%
“…Gore-Tex is known to be a safe implant material [1][2][3]. However, its use may lead to clinical problems.…”
Section: Sirmentioning
confidence: 99%
See 1 more Smart Citation